Shaping complex functional communication responses. Issue 3 (14th May 2018) - Ghaemmaghami, Mahshid; Hanley, Gregory P.; Jessel, Joshua; Landa, Robin
Abstract : Response efficiency plays an important role in the initial success of functional communication training (FCT). Although low‐effort functional communication responses (FCRs) have been shown to be most effective in replacing problem behavior; more developmentally advanced FCRs are favored later in the treatment process. Attempts to teach these more complex FCRs, however, often lead to the resurgence of problem behavior. In this study, we provide a detailed description of an effective shaping process applied within a changing criterion design to develop complex FCRs from simple FCRs without resurgence of problem behavior. Four children with various language and intellectual abilities participated in this study. A practical shaping procedure, suitable for typical teaching contexts, is described for two participants in Experiment 1. The necessity and efficacy of the shaping process are demonstrated with the participants in Experiment 2. Implications for practice and research are discussed.